Tall Tale and Anti-Capitalist (Post) Western Storytelling in Douglas Coupland's Generation X. - Tian, Junwu; Duan, Yingjie (Western American Literature)
Douglas Coupland's novel Generation X: Tales for an Accelerated Culture explores the importance of storytelling in society through the characters of Andy, Dag, and Claire. Set in Palm Springs, California, the characters share autobiographical and whimsical stories while working low-rent service industry jobs. The novel delves into the effects of corporate capitalism and technocapitalism on the US West, while also touching on themes of the decline of atomic optimism and the postwestern nature of the American West. Coupland incorporates paratexts, such as illustrations and notes in the margins, which serve as a commentary on the novel's actions and ideas, reflecting the future of storytelling in the digital age.